Symbolic interactionism theory - Mawla, Najah; Almohamedaoi, Ali (Al-Adab Journal, 2024)
Symbolic interactionism is useful in understanding how symbols are exchanged and help construct effective meaning between individuals. As such, they constitute influences on building individual and cultural identities. The theory of symbolic interactionism provides an analysis of the social impact of symbols and messages on society. Language forms the basis of the theory in explaining all impressions and social experiences resulting from the symbol. Symbolic interaction theory plays an important role in attempts to understand the self. Through the symbolic exchange of messages and symbols, individuals can construct an image of themselves and define their social identities. It also allows individuals to contribute to building their identity through symbolic interactions and the use of language and symbols. As well as promoting self-awareness, which helps in understanding how symbols are used to express themselves and determine their positions in society. In general, the focus on symbolic interactions provides effective tools for individuals to understand themselves and analyze their social situations and experiences.